2011
DOI: 10.1177/1040638711403404
|View full text |Cite
|
Sign up to set email alerts
|

Experimental interspecies transmission studies of the transmissible spongiform encephalopathies to cattle

Abstract: Abstract. Prion diseases or transmissible spongiform encephalopathies (TSEs) of animals include scrapie of sheep and goats; transmissible mink encephalopathy (TME); chronic wasting disease (CWD) of deer, elk and moose; and bovine spongiform encephalopathy (BSE) of cattle. The emergence of BSE and its spread to human beings in the form of variant Creutzfeldt-Jakob disease (vCJD) resulted in interest in susceptibility of cattle to CWD, TME and scrapie. Experimental cross-species transmission of TSE agents provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 110 publications
(210 reference statements)
0
29
0
8
Order By: Relevance
“…The retina is the most accessible part of the CNS and is amenable to non-invasive assessment of morphology and function. We have previously demonstrated that functional changes develop in the retina of cattle inoculated with transmissible mink encephalopathy, a TSE with microscopic features similar to those of BSE [28], months prior to other clinical signs of disease [24]. Here we describe changes in retinal morphology and function over time in animals inoculated with two different strains of BSE; classical foodborne BSE, which transmits to humans as vCJD [6,29,30], and atypical high-type BSE (BSE-H) diagnosed in the US in 2004 [31].…”
Section: Introductionmentioning
confidence: 99%
“…The retina is the most accessible part of the CNS and is amenable to non-invasive assessment of morphology and function. We have previously demonstrated that functional changes develop in the retina of cattle inoculated with transmissible mink encephalopathy, a TSE with microscopic features similar to those of BSE [28], months prior to other clinical signs of disease [24]. Here we describe changes in retinal morphology and function over time in animals inoculated with two different strains of BSE; classical foodborne BSE, which transmits to humans as vCJD [6,29,30], and atypical high-type BSE (BSE-H) diagnosed in the US in 2004 [31].…”
Section: Introductionmentioning
confidence: 99%
“…Cattle failed to develop SE although PrP res was detected in the CNS (Hamir et al, 2011). In sheep, only two of eight became infected: one (ARQ/VRQ at codons 136, 154, and 171) developing clinical signs, SE lesions and was PrP res positive at 35 months post inoculation (mpi) and one (ARQ/ARQ) SE and PrP res positive but no clinical signs at 72 months pi; two ARQ/ARQ and four ARQ/ARR were negative for PrP res at 36-72 mpi (Hamir et al, 2006b).…”
Section: Host Rangementioning
confidence: 88%
“…In sheep, only two of eight became infected: one (ARQ/VRQ at codons 136, 154, and 171) developing clinical signs, SE lesions and was PrP res positive at 35 months post inoculation (mpi) and one (ARQ/ARQ) SE and PrP res positive but no clinical signs at 72 months pi; two ARQ/ARQ and four ARQ/ARR were negative for PrP res at 36-72 mpi (Hamir et al, 2006b). Oral transmission into cattle failed (to nine years post infection) (Hamir et al, 2011).…”
Section: Host Rangementioning
confidence: 93%
See 1 more Smart Citation
“…25 Cattle orally inoculated with CWD-infected brains, or housed with CWD-positive deer, do not contract a TSE but cattle inoculated intracerebrally with CWD do develop a prion disease. 18,26 This highlights the potential, given the correct circumstances, for CWD to overcome this species barrier. Prion disease transmission from cervids to cattle could also occur through any number of intermediate species.…”
Section: Chronic Wasting Diseasementioning
confidence: 93%